Feresa attenuata Gray 1874 - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Feresa attenuata Gray, 1874 —Pygmy Killer Whale Feresa attenuata Gray, 1874 p.238; Type locality- South Seas; Kim et al. , 2000 p.88; Kim, 2004 p.239. Range: Since F. attenuata rarely enters the waters of Korea, vagrant might better fit the distribution status of this species (Fig. 96). Remarks: The pygmy killer whale is a monotypic species with low genetic diversity across its range (Burbidge et al . 2012). Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, distribution and conservation status, pp. 1-216 in Zootaxa 4522 (1) on page 144, DOI:10.11646/zootaxa.4522.1.1, http://zenodo.org/record/2610198